Amplification and restriction endonuclease digestion of a large fragment of genes coding for rRNA as a rapid method for discrimination of closely related pathogenic bacteria. - Ibrahim, A (1996)
By use of primers specific to conserved regions of the rRNA gene cluster, a discrete amplicon of approximately 5 kb was amplified by PCR from all 21 bacterial genera investigated. Subsequent endonuclease digestion of the PCR product with HaeIII distinguished between the three species of the human pathogen Francisella spp. on the one hand and four clinically relevant genomic groups of Acinetobacter spp. on the other hand. The described technique has the potential as a rapid method for discriminating between closely related species that are of clinical importance.